2019
DOI: 10.1002/gps.5231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an intervention to support hearing and vision in dementia: The SENSE‐Cog Field Trial

Abstract: Objectives Hearing, vision, and cognitive impairment commonly co‐occur in older adults. Improving sensory function may positively impact outcomes in people with dementia (PwD). We developed a “sensory intervention” (SI) to support hearing and vision in PwD. Here, we report the findings of an international open‐label field trial, and nested case series, to explore the impact of the SI on dementia‐related outcomes. Methods This was a home‐based trial conducted in France, England, and Cyprus. Participants were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 40 publications
(86 reference statements)
0
74
0
Order By: Relevance
“…Adherence support for PwD with sensory devices will enhance hearing [29], vision [30], or both [15].…”
Section: • Causal Assumptions About How Change Will Be Producedmentioning
confidence: 99%
“…Adherence support for PwD with sensory devices will enhance hearing [29], vision [30], or both [15].…”
Section: • Causal Assumptions About How Change Will Be Producedmentioning
confidence: 99%
“…Adherence support for PwD with sensory devices will enhance hearing [29], vision [30], or both [15]. Furthermore, social opportunities will be enhanced through signposting outside the home, thus addressing social isolation, improving social relationships, and providing respite for companions.…”
Section: Causal Assumptions About How Change Will Be Producedmentioning
confidence: 99%
“…Another strength of our approach includes the sound theoretical framework on which the intervention was developed, and the iterative manner in which it was modified and field-tested [12,15] before arriving at the final version of the intervention, ready for full scale effectiveness testing. A limitation (although also a potential strength) is the significant degree of variability in the study sites due to the different EU contexts in which the programme takes place, as well as the variability of the intervention offered to each participant dyad, resulting from the tailored approach.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related hearing loss may be associated with an increased risk of dementia in later life, which has garnered increasing attention as a potentially modi able risk factors for dementia and cognitive decline [10][11][12]. Evidence from a randomized controlled trial regarding hearing support in dementia (i.e., SENSE-Cog Field Trial) demonstrated that employing a sensory intervention to support hearing, such as providing hearing aids, communication training, and supplementary sensory aids to enhance the home environment or foster social inclusion, bene ts people with dementia as well as their partner by improving their quality of life, physical functions, psychosocial health and relationship satisfaction [15,16]. Moreover, studies have indicated that hearing aid use confers a mitigating effect on the trajectories of cognitive decline by maintaining cognitive function, such as episodic memory [17,18].…”
Section: Introductionmentioning
confidence: 99%